2018
DOI: 10.1002/ajpa.23447
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dental tissues to sex determination in modern human populations

Abstract: Our results suggest that the 3D variables from mandibular canine dental tissues are useful for sex determination as they present a high degree of dimorphism. The results obtained show the importance of 3D dental tissue measurements as a methodology in sex determination, which application should be considered as a supplemental method to others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
81
2
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(105 citation statements)
references
References 85 publications
(153 reference statements)
14
81
2
8
Order By: Relevance
“…In consequence, these formulae can be used for sex estimation with reliance on samples phenotypically related to the identified skeletons of the University of Coimbra. On the other hand, the percentages of correct allocation given by the discriminant functions (77.42–86.54%) and the logistic regressions (81.63–85.18%) are similar to those obtained by previous research considering different measurements in samples around the world (e.g., Isçan & Kedici, for Turks: 73–77%; Acharya & Mainali, for Nepalese: 77.4–83%; Viciano et al, for Spaniards: 79.4–92.6%; Khamis et al, for Malaysians: 70.2–78.5%; Viciano et al, for archaeological Italians: 83.7–95.9%; and García‐Campos et al, for a modern sample from Spain, South Africa, and Sudan: 71.43–84.62%). These findings confirm the usefulness of permanent canine measurements for sex estimation in specific populations and the need to test their applicability in geographically‐related samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In consequence, these formulae can be used for sex estimation with reliance on samples phenotypically related to the identified skeletons of the University of Coimbra. On the other hand, the percentages of correct allocation given by the discriminant functions (77.42–86.54%) and the logistic regressions (81.63–85.18%) are similar to those obtained by previous research considering different measurements in samples around the world (e.g., Isçan & Kedici, for Turks: 73–77%; Acharya & Mainali, for Nepalese: 77.4–83%; Viciano et al, for Spaniards: 79.4–92.6%; Khamis et al, for Malaysians: 70.2–78.5%; Viciano et al, for archaeological Italians: 83.7–95.9%; and García‐Campos et al, for a modern sample from Spain, South Africa, and Sudan: 71.43–84.62%). These findings confirm the usefulness of permanent canine measurements for sex estimation in specific populations and the need to test their applicability in geographically‐related samples.…”
Section: Discussionsupporting
confidence: 88%
“…In these contexts, teeth are valuable and useful tools for sex estimation (Ling & Wong, 2007). Numerous methodologies based on canine metrics have been proposed for archaeological and forensic samples throughout the world, with satisfactory results (e.g., Acharya & Mainali, 2007;Aris, Nystrom, & Craig-Atkins, 2018;García-Campos et al, 2018;Isçan & Kedici, 2003;Karaman, 2006;Khamis, Taylor, Malik, & Townsend, 2014;Kieser, 2008;Mitsea, Moraitis, Leon, Nicopoulou-Karayianni, & Spiliopoulou, 2014;Okazaki, 2005;Saunders, Chan, Kahlon, & Kluge, 2007;Thompson, 2013;Viciano, D'Anastasio, & Capasso, 2015;Viciano, López-Lázaro, & Alemán, 2013;Zorba, Moraitis, Eliopoulos, & Spiliopoulou, 2012;Zorba, Moraitis, & Manolis, 2011;Zorba, Vanna, & Moraitis, 2014). However, as the degree of sexual dimorphism varies among different samples, their application is usually restricted to the population in which it was created (Cardoso, 2010;Hillson, 1986;Kondo & Townsend, 2004;Luna, 2008Luna, , 2010Luna, , 2012Luna, , 2015Pereira, Bernardo, Pestana, Santos, & Mendonça, 2010;Roberts & Manchester, 1999;Saunders et al, 2007;Schwartz & Dean, 2005).…”
mentioning
confidence: 99%
“…It has been argued that 3D measurements offer a more accurate method to investigate tissue proportions because enamel thickness is not homogenous across the molar crown and therefore 2D measurements likely do not reflect whole‐crown enamel volumes reliably (Benazzi et al, ; Feeney, ; García‐Campos et al, ). On the other hand, tooth wear has a greater effect on 3D measurements, which is more difficult to correct than in 2D sections (Smith et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were differences between the upper and lower jaws: females had significantly greater relative enamel thickness (RET) in mandibular second and third molars, but not in their maxillary isomeres. Recent research by García‐Campos et al () examining dental tissues of mandibular canines has shown that, except for enamel cap area and volume, all dental measurements (both 3D volumes and 2D surface areas) are significantly larger in males, and in particular, males have absolutely and proportionally greater quantities of dentine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation